Shear Behaviour of Continuous Tapered Steel Plate Girders with Corrugated Webs - Mohamed Dabaon; Ahmed El-Hadidy; Rashad Manaa (Journal of Engineering Research - Egypt)
During previous years, so many attempts have been made to reduce the own weight of the steel members used in bridges, as well as reducing the cost of construction. One of these attempts is to use tapered (i.e. non-prismatic with varying depth) steel plate girders with corrugated webs (TPGCWS). The corrugated steel plates are widely used as structural elements in many structural applications because of their numerous favourable properties compared with traditional flat plates. Moreover, they have been used due to their aesthetical appearance, especially in the case of TPGCWs. So many researches have been made to investigate the shear behaviour of TPGCWS for the case of simple girder, to the author’s knowledge, no one has investigated the shear behaviour of TPGCWS for the case of continuous girder. So, the aim of this paper is to investigate the shear behaviour of TPGCWS for the case of continuous girder. Two experimental models have been tested to verify the finite element (FE) analysis and compare the experimental results with FE results and the existing design equations.